Zoological exhibitions in natural history museums: classic design and modern approach - Igor Evstafiev (Theriologia Ukrainica)
Traditional natural history museums display elaborate stuffed animals in showcases or as part of dioramas. Classic diorama displays are three-dimensional images, with a combination of natural objects and artworks depicting a natural setting. The basis of a zoological diorama is a realistic image of the landscape (a photograph or painting depicting a certain landscape), which serves as a background for the main objects of the exhibition. To create a realistic atmosphere, natural materials such as soil, stones, plants, and trees are used, and stuffed animals in dioramas are made in dynamic poses typical of the species. This means of recreating a part of the natural environment helps to demonstrate the peculiarities of the ecosystem and the atmosphere itself in which the represented animal species live. The author, who has been visiting zoological museums in different cities and countries for many years, has had the opportunity to observe the emergence of fundamentally new approaches to exhibition activities in modern museums, and the impetus was his acquaintance with the Grande Galerie de l’Évolution in Paris, which is part of the Muséum National d’Histoire Naturelle. The Evolution Gallery exhibition is a vivid example of a new approach that skilfully combines the display of stuffed animals and modern technologies to convey information about the principles of evolution, biodiversity, and the role of animals in ecosystems. The Gallery widely uses such technologies as multimedia displays, interactive panels, mobile applications, etc. In fact, the further development of zoological exhibitions is determined by scientific and technological progress, and the development of digital technologies (high-quality cameras, drone technology, and smartphones) has made the process of nature photography more accessible. This provides endless possibilities for involving such materials in exhibition activities, which is facilitated by the variety of social networks and various aggregators of visual and audio information available for exchange and use. Therefore, the production and display of new biogroups and dioramas requires the mandatory use of modern technologies, which increases the attractiveness of the exposition for the modern museum visitor. The most successful examples of the use of new approaches in the design of the exposition are presented and analysed.